Development of an Innovative Process for High-Temperature Fruit Juice Extraction Using a Novel Thermophilic Endo-Polygalacturonase From Penicillium oxalicum - Cheng, Zhong; Xian, Liang; Chen, Dong; Lu, Jian; Wei, Yutuo; Du, Liqin; Wang, Qingyan; Chen, Yunlai; Lu, Bo; Bi, Dewu; Zhang, Zhikai; Huang, Ribo (Frontiers in Microbiology, 2020)
Efficient and cost-effective production of thermophilic endo-polygalacturonase is desirable for industrial fruit juice production, because its application could shorten the processing time and lower the production cost, by eliminating the separate step of pectin degradation. However, no endo-polygalacturonase that both functions well at sufficiently high temperature and can be manufactured economically, has been reported previously. In this study, the cDNA encoding a thermophilic endo-polygalacturonase from Penicillium oxalicum CZ1028, was cloned and over-expressed in Pichia pastoris GS115 and Escherichia coli BL21(DE3). The recombinant proteins PoxaEnPG28B-Pp (from P. pastoris) and PoxaEnPG28B-Ec (from E. coli) were isolated and purified. PoxaEnPG28B-Pp was sufficiently thermostable for potential industrial use, but PoxaEnPG28B-Ec was not. The optimal pH and temperature of PoxaEnPG28B-Pp were pH 5.0 and 65 °C, respectively. The enzyme had a low Km of 1.82 g/L and a high Vmax of 77882.2 U/mg, with polygalacturonic acid (PGA) as substrate. The performance of PoxaEnPG28B-Pp in depectinization of papaya, plantain and banana juices at 65 °C for 15 min was superior to that of a reported mesophilic endo-polygalacturonase. PoxaEnPG28B-Pp is the first endo-polygalacturonase reported to show excellent performance at high temperature. An innovative process, including a step of simultaneous heat-treatment and depectinization of fruit pulps with PoxaEnPG28B-Pp, is reported for the first time.